Social Accountability in Non-Profit Institutions: The Stakeholder Theory Approach in Social Impact-Based Reporting - Tommy Ferdian; Ronald N Girsang (PT. Anagata Sembagi Education, 2025)
Social accountability is a key foundation for the legitimacy and sustainability of non-profit organizations. However, participatory and impact-based social reporting practices have not been fully adopted systematically. This study aims to analyze the influence of a stakeholder approach on the quality of social impact-based reporting in non-profit organizations. Using a quantitative approach and the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method, this study involved 127 respondents from various non-profit organizations in Indonesia that actively publish social reports. The analysis results show that a stakeholder approach that includes participation, dialogue, information disclosure, and responsiveness has a significant influence on the quality of social reporting (β = 0.681; p < 0.001; R² = 46.4%). This finding supports stakeholder theory and strengthens the argument that effective social reporting depends on the active involvement of stakeholders throughout the program management process. Practically, this study suggests the need to strengthen the capacity of participatory impact-based reporting and adopt stakeholder engagement mechanisms as part of organizational governance. Thus, social reporting is not only a technical instrument, but also a strategic means to build legitimacy, transparency, and sustainable relationships with the community.